Evaluation of a mental health outreach service for homeless families. Issue 3 (1st March 2002) - Tischler, V; Vostanis, P; Bellerby, T; Cumella, S
Abstract : Aims: To describe the characteristics of homeless children and families seen by the mental health outreach service (MHOS), to evaluate the impact of this service on the short term psychosocial functioning of children and parents, and to establish perceptions of, and satisfaction with, the service. Methods: Twenty seven children from 23 families who were in receipt of the MHOS and 27 children from 23 families residing in other hostels where no such service was available were studied. The MHOS was delivered by a clinical nurse specialist with expertise in child mental health, who offered the following interventions: assessment and brief treatment of mental health disorders in children; liaison with agencies; and training of homeless centre staff. Results: Children in the experimental group had a significantly higher decrease in Strengths and Difficulties Questionnaire (SDQ) total scores. Having received the intervention was the strongest predictor of improvement in SDQ total scores. There was no significant impact on parental mental health (General Health Questionnaire) scores. Homeless families and staff expressed high satisfaction with the MHOS. Conclusion: This MHOS for homeless families is an innovative intervention which meets the complex and multiple needs of a vulnerable population unable to access mainstream mental health services. The primary objective of the service was to improve child mental health problems; however, the service developed in a responsive way by meeting social and practical needs of families in addition to its clinical role.